2019
DOI: 10.1002/hbm.24775
|View full text |Cite
|
Sign up to set email alerts
|

Anosognosia and default mode subnetwork dysfunction in Alzheimer's disease

Abstract: Research on the neural correlates of anosognosia in Alzheimer's disease varied according to methods and objectives: they compared different measures, used diverse neuroimaging modalities, explored connectivity between brain networks, addressed the role of specific brain regions or tried to give support to theoretical models of unawareness. We used resting‐state fMRI connectivity with two different seed regions and two measures of anosognosia in different patient samples to investigate consistent modifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 65 publications
(101 reference statements)
8
40
1
Order By: Relevance
“…A study conducted by Berlingeri et al (2015) found significant functional connectivity reduction in unaware AD patients within the inferior medial temporal cortex (IMTC) and VMPFC networks, but only disconnection between IMTC and hippocampus and insular cortex correlated with anosognosia severity. Finally, a more recent study reported that memory awareness correlated with the degree of disconnection between hippocampus and retrosplenial cortex extending to the ventral PCC and right posterior inferior parietal lobe; in addition, anosognosia was associated with decreased connectivity between hippocampus and VMPFC (Antoine et al, 2019).…”
Section: The Role Of the Frontal Lobes Revisitedmentioning
confidence: 94%
“…A study conducted by Berlingeri et al (2015) found significant functional connectivity reduction in unaware AD patients within the inferior medial temporal cortex (IMTC) and VMPFC networks, but only disconnection between IMTC and hippocampus and insular cortex correlated with anosognosia severity. Finally, a more recent study reported that memory awareness correlated with the degree of disconnection between hippocampus and retrosplenial cortex extending to the ventral PCC and right posterior inferior parietal lobe; in addition, anosognosia was associated with decreased connectivity between hippocampus and VMPFC (Antoine et al, 2019).…”
Section: The Role Of the Frontal Lobes Revisitedmentioning
confidence: 94%
“…According to this view, reduced connectivity of the default mode network (DMN), seen in the early phases of AD (Klaassens et al, 2017), may act as a marker of progression associated with anosognosia (Therriault et al, 2018). In fact, the bases of impaired selfawareness and anosognosia have been heavily intertwined to the functionality of the DMN in AD (Antoine et al, 2019;Mondragon, Maurits & Deyn, 2019) and other neurological conditions, such as anosognosia for hemiplegia (Pacella et al, 2019). On these grounds, the DMN could be conceived as a translational construct to justify a routine assessment in the preclinical stage of AD (Cacciamani et al, 2017).…”
Section: Association Between Anosognosia and Brain Structurementioning
confidence: 99%
“…Several of these regions belong to the Default Mode Network (DMN), which supports cognitive processing of the self and autobiographical memory (50). Accordingly, lack of awareness in AD is also associated with decreased functional connectivity between brain areas within the DMN or between DMN and other brain regions (51)(52)(53)(54). Interpreted at the light of the Cognitive Awareness Model, the neural correlates of anosognosia in AD suggest that several difficulties can explain lack of awareness for memory deficits in the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interpreted at the light of the Cognitive Awareness Model, the neural correlates of anosognosia in AD suggest that several difficulties can explain lack of awareness for memory deficits in the patients. Decreased connectivity between frontal, temporal, and parietal areas on the one hand and medial temporal lobe regions on the other hand would contribute to failure of updating the personal knowledge base; medial prefrontal and posterior cingulate damage would affect the efficacy of self-referential processing during explicit performance evaluation; and deficient error monitoring caused by damage to the anterior cingulate cortex and insula would disturb comparator mechanisms ( 51 , 55 ).…”
Section: Introductionmentioning
confidence: 99%